Food security in ASEAN: progress, challenges and future - Sundram, Pushpanathan (Frontiers in Sustainable Food Systems, 2023)
This article examines the progress, challenges and future of food security in the Association of Southeast Asian Nations (ASEAN) region. The COVID-19 pandemic has exposed the fragility of ASEAN food systems, exacerbating existing challenges and vulnerabilities. With a focus on addressing the pressing issue of ensuring sufficient, affordable, and nutritious food for its growing population, the article explores the multifaceted challenges of food security faced by ASEAN. It emphasises the need for an integrated approach to address the impact of climate change, investment in rural infrastructure and agricultural research, and the promotion of sustainable and inclusive agriculture for ASEAN's long-term food security. It also underscores the importance of collaboration with international partners and organisations to leverage expertise and resources. Overall, this article calls to action policymakers, stakeholders and external partners to collectively work towards achieving food security and sustainable development in the region.